(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
The purpose of this research is to know the extent of the influence of communication internal against the effectiveness of the sevices in the Office of the head of Mandolang District Minahasa in North Sulawesi Province. This research using quantitative research methods. With the samples used is Saturated Sampling are 35 people. Based on a simple linier regression analysis showed that there is influence of internal communication between (X) and (Y) work efficiency. It is evident simple linier regression equation of Y=14,613 + 0,538 X + e. for calculation of the correlation relationship is category of being, This evidenced by the r value 0,565 interpretation advanced by Sugiono are in the interval (0,00-0,199). And the value of the coefficient of determination is 31,9% indicating that the influence of internal commucation against the effectiveness of the service namely 31,9% and the rest is 68,1% influenced by variables that are not included in this research. From the results of the comparism of the value of a sig (0,03) a (0,05) these authors conclude that internal influential communication significantly to the effectiveness of the sevices Head Office Mandolang in the Regency of Minahasa in North Sulawesi province. Then the hypothesis in this study was accepted H1and H0 denied. Keywords: Internal Communication, The Services Effectiveness